Rethinking Technology-Driven CPD (Continuing Professional Development) for Arabic Language Teachers in Indonesia - Akmalia, Frida; Andriyanti, Erna; Triyono, Sulis (Asalibuna, 2025)
Abstract: Amid the global shift toward digital education, the professional growth of teachers is increasingly shaped by their ability to integrate technology into pedagogical practice. However, Arabic language teachers often face systemic barriers in accessing relevant and effective technology-driven professional development. This conceptual paper investigates the underexplored intersection between educational technology and Continuing Professional Development (CPD) for Arabic language educators, particularly in the context of Indonesia. Drawing on Technological Pedagogical Content Knowledge (TPACK), Professional Competence Theory, and Andragogy, the study proposes a contextualized CPD framework that addresses the unique instructional demands of Arabic teaching. It critically analyzes current limitations in teacher training such as low digital literacy, limited subject-specific support, and a mismatch between CPD content and classroom realities. Moreover, the paper underscores the scarcity of scholarly attention to Arabic teacher development in the broader discourse on technology-enhanced learning. By bridging theory and practice, this article contributes a model for inclusive and sustainable CPD that empowers Arabic teachers to design more engaging and culturally relevant learning experiences. The proposed framework has implications for educational policy, curriculum design, and future empirical research in multilingual and digitally evolving contexts.   Abstrak: Di tengah pergeseran global menuju pendidikan digital, pertumbuhan profesional guru semakin dibentuk oleh kemampuan mereka untuk mengintegrasikan teknologi ke dalam praktik pedagogi. Namun, guru bahasa Arab sering menghadapi hambatan sistemik dalam mengakses pengembangan profesional berbasis teknologi yang relevan dan efektif. Artikel konseptual ini menyelidiki persimpangan yang belum dieksplorasi antara teknologi pendidikan dan Pengembangan Keprofesian Berkelanjutan (PKB) untuk pendidik bahasa Arab, khususnya dalam konteks Indonesia. Dengan mengacu pada TPACK, Teori Kompetensi Profesional, dan Andragogi, penelitian ini mengusulkan kerangka kerja PKB kontekstual yang membahas tuntutan instruksional yang unik dari pengajaran bahasa Arab. Studi ini secara kritis menganalisis keterbatasan saat ini dalam pelatihan guru seperti literasi digital yang rendah, dukungan mata pelajaran yang terbatas, dan ketidaksesuaian antara konten PKB dan realitas di kelas. Selain itu, artikel ini menggarisbawahi kelangkaan perhatian para akademisi terhadap pengembangan guru bahasa Arab dalam wacana yang lebih luas tentang pembelajaran yang ditingkatkan dengan teknologi. Dengan menjembatani teori dan praktik, artikel ini memberikan kontribusi berupa model PKB yang inklusif dan berkelanjutan, yang memberdayakan para guru bahasa Arab untuk merancang pengalaman belajar yang lebih menarik dan relevan secara budaya. Kerangka kerja yang diusulkan memiliki implikasi untuk kebijakan pendidikan, desain kurikulum, dan penelitian empiris di masa depan dalam konteks multibahasa dan perkembangan digital.